Comparative administrative law - Rose-Ackerman, Susan, 1942-; Lindseth, Peter L., 1962-; Emerson, Blake (Cheltenham : Edward Elgar Publishing, 2017)
A comprehensive overview of the field of comparative administrative law that builds on the first edition with many new and revised chapters, additional topics and extended geographical coverage. This Research Handbook's broad, multi-method approach combines history and social science with more strictly legal analyses. This new edition demonstrates the growth and dynamism of recent efforts - spearheaded by the first edition - to stimulate comparative research in administrative law and public law more generally, reaching across different countries and scholarly disciplines. A particular focus is on administrative independence with its manifold implications for separation of powers, democratic self-government, and the boundary between law, politics, and policy. Several chapters highlight the tensions between impartial expertise and public accountability; others consider administrative litigation and the role of the courts in reviewing both individual decisions and secondary norms. The book concludes by asking how administrative law is shaping and is being shaped by the changing boundaries of the state, especially shifting boundaries between the public and the private, and the national and the supranational domains. This extensive and interdisciplinary appraisal of the field will be a vital resource for scholars and students of administrative and comparative law worldwide, and for public officials and representatives of interest groups engaged with government policy implementation and regulation.
Introduction / Susan Rose-Ackerman, Peter Lindseth, and Blake Emerson -- Part I constitutional structure and administrative law : traditions and transformations -- 1. Révolution, rechtsstaat and the rule of law : historical reflections on the emergence and development of administrative law / Bernardo Sordi -- 2. Good-bye, Montesquieu [reprint] / Bruce Ackerman -- 3. Politics and agencies in the administrative state : the U.S. case / Peter Strauss -- 4. Written constitutions and the administrative state : on the constitutional character of administrative law [reprint] / Tom Ginsburg -- 5. Comparative positive political theory and empirics / M. Elizabeth Magill and Daniel R. Ortiz -- 6. The neue verwaltungsrechtswissenschaft against the backdrop of traditional administrative law scholarship in Germany / Andreas Voßkuhle and Thomas Wischmeyer -- 7. Transformations of administrative law : Italy from a comparative perspective / Marco D'Alberti ---8. Hungary's post-socialist administrative law regimes / Krisztina Kovács and Kim Lane Scheppele -- Part II administrative independence -- 9. The promise of comparative administrative law : a constitutional perspective on independent agencies [reprint] / Daniel Halberstam -- 10. The puzzle of independence and parliamentary democracy in the common law world : a Canadian perspective / Lorne Sossin -- 11. Assessing the theory of presidential dominance : empirical evidence of the relationship between the executive branch and regulatory agencies in Brazil / Mariana Mota Prado -- 12. Experimenting with independent commission in a new democracy with a civil law tradition : the case of Taiwan / Jiunn-Rong Yeh -- 13. Flag-bearers of a new era? : the evolution of new regulatory institutions in India (1991-2016) / Arun Kumar Thiruvengadam -- 14. A comparison of us and European independent commissions / Martin Shapiro -- Part III transparency, procedure, and policy-making ---15. Citizens and technocrats : an essay on trust, public participation, and government legitimacy / Susan Rose-Ackerman -- 16. The rise of reason giving in American administrative law / Jerry Mashaw -- 17. The 2015 French code of administrative procedure : an assessment / Dominique Custos -- 18. Three generations of administrative procedures / Javier Barnes -- 19. Administrative agencies as creators of administrative law norms : evidence from the UK, France and Sweden [reprint] / Dorit Rubinstein Reiss -- 20. Comparing regulatory oversight bodies : the US office of information and regulatory affairs and the EU regulatory scrutiny board / Jonathan B. Wiener and Alberto Alemanno -- 21. Looking for smarter government (and administrative law) in the age of uncertainty / Giulio Napolitano -- 22. Participation and expertise : judicial attitudes in comparative perspective / Catherine Donnelly -- Part IV administrative litigation and administrative law ---23. Judicial review of questions of law : a comparative perspective / Paul Craig -- 24. Proportionality review in administrative law / Jud Mathews -- 25. Voidness and voidability of unilateral administrative acts in the western tradition / Gabriel Bocksang Hola -- 26. The powers and duties of the French administrative judge / Jean Massot -- 27. Judicial review of agency action in the US and Israel : the choice between open and closed review / Michael Asimow and Yoav Dotan -- 28. The 'double helix' of process and substance review before the UK competition appeal tribunal : a model case or a cautionary tale for specialist courts? / Athanasios Psygkas -- 29. Judicial deference to agency's discretion in new democracies : observations on constitutional decisions in Poland, Taiwan, and South Africa / Cheng-Yi Huang -- 30. Legal management of urban space in Japan and the role of the judiciary / Narufumi Kadomatsu ---31. The courts and public space : France, the UK and the US in historical perspective / Thomas Perroud -- Part V administrative law and the boundaries of the state : a. public and private -- 32. Three questions of privatization [reprint] / Daphne Barek-Erez -- 33. Contracting out and 'public values' : a theoretical and comparative approach [reprint] / Jean-Bernard Auby -- 34. Organizational structure and culture in an era of privatization : the case of United States military and security contractors / Laura A. Dickinson -- 35. Transnational non-state regulation and domestic administrative law / Victor V. Ramraj -- b. administrative law beyond the state : the case of the EU -- 36. A framework for historical comparison of control of national, supranational and transnational public power / Peter Cane -- 37. EU agencies 2.0 : the new constitution of supranational administration beyond the EU commission / Johannes Saurer ---38. Administrative discretion in the EU : comparative perspectives / Joana Mendes -- 39. Administrative law reform in the European Union : the reneual project and its basis in comparative legal studies / Herwig C.H. Hofmann and Jens-Peter Schneider -- 40. The constitutional basis of EU administrative law / Matthias Ruffert -- 41. What's in a label? : the EU as "administrative" and "constitutional" / Peter L. Lindseth -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: správní právo; srovnávací právní věda; administrative law; comparative law; e-knihy online; e-books online